Pengaruh Pengetahuan Kewirausahaan, Motivasi Kewirausahaan, Efikasi Diri dan Lingkungan Keluarga Terhadap Minat Wirausaha Mahasiswa - Nadia Farah Dina; Erma Setiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Entrepreneurial knowledge, motivation to become an entrepreneur, self-efficacy, and support from the family environment are important factors in efforts to reduce unemployment and encourage entrepreneurial spirit among students. This study aims to analyze the influence of these four factors on the entrepreneurial interest of undergraduate students in Accounting study programs at the Faculty of Economics and Business, Muhammadiyah University of Surakarta, Sebelas Maret University, and Batik Islamic University. This study uses a quantitative approach with a correlational method. Data collection techniques are carried out by distributing questionnaires. The population in this study was 115 students of the 2021 intake from the Accounting study program, with a sample of 53 students. Data were obtained through questionnaires and analyzed using instrument tests (validity and reliability), classical assumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis tests (T test and F test). The results showed that entrepreneurial motivation and family environment have a significant influence on students' interest in entrepreneurship. Meanwhile, entrepreneurial knowledge and self-efficacy did not show a significant influence on this interest.